A study on physico-chemical parameters of Urinjikulam Pond, Thiruthangal (Virudhunagar District, Tamil Nadu) - J Arun Raj; SP Sevarkodiyone (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2018)
Present paper deals with the study of Physico-chemical parameters of Urinjikulam pond, Thiruthangal (Virudhunagar district, Tamil Nadu). Monthly variations in the physical and chemical parameters such as temperature, pH (7.5 to 8.8), dissolved oxygen (1.62-5.92 mg/L), total alkalinity (81-271mg/L), total hardness (48 to 364mg/L), chlorides (11 to 1030mg/L), Phosphate (0.36 to 2.86mg/L) and nitrate (0 to 0.40mg/L) were investigated. All the parameters were beyond the permissible limits.